1.2-1.9x=0.5(x+3)-0.3(x+5)

Simple and best practice solution for 1.2-1.9x=0.5(x+3)-0.3(x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1.2-1.9x=0.5(x+3)-0.3(x+5) equation:


1.2-1.9x=0.5(x+3)-0.3(x+5)

We simplify the equation to the form, which is simple to understand
1.2-1.9x=0.5(x+3)-0.3(x+5)

Reorder the terms in parentheses
1.2-1.9x=+( + 0.5x+1.5)-0.3*(x+5)

Remove unnecessary parentheses
+1.2-1.9x=0.5x+1.5-0.3+*(+x+5+)

Reorder the terms in parentheses
1.2-1.9x=0.5x+1.5+(-0.3x-1.5)

Remove unnecessary parentheses
+1.2-1.9x=0.5x+1.5-0.3x-1.5

We move all terms containing x to the left and all other terms to the right.
-1.9x-0.5x + 0.3x=+1.5-1.5-1.2

We simplify left and right side of the equation.
-2.1x=-1.2

We divide both sides of the equation by -2.1 to get x.
x=0.57142857142857

See similar equations:

| y=3x+68 | | 67(k+79)=313 | | -2x+11=8 | | 6x=-11x-3 | | f(x)=-0.02x^2+x+5.75 | | 7x-11=4x-2 | | 3x+1.5=4.6 | | d/dx((1000)(1.03^x)) | | 175(330-x)+90x=39560 | | 4x^2-y^2+4y-5=0 | | -30=-6g | | -2/3x-4 | | 10x+2=12x+4 | | x=11+4y(-2) | | 1-3(x+8)=-2x-18 | | lne^3x=22 | | (x+(8-3i))(x+(8+3i))=0 | | -5r-29=7(8-4r)+6r | | lne^3x-2=22 | | 5x-5=4x-10 | | 7x-5=3x-6 | | -5(a-8)=5+2a | | 3b-(1+b)=6b+21 | | 2y-(11+4y)=-7 | | x^2+5x=22 | | -9-3p=p+3(-2p+1) | | 98v^2+56v+8=0 | | x^2+x+25+y^2+4y+y=49 | | (5W+7)-(5W+1)= | | 6x^3-x-1=0 | | X^2-5+25+y^2+4y-2=49 | | -4m=3(m-9) |

Equations solver categories